Requiem for Miranda: The Rehnquist Court's Voluntariness Doctrine in Historical Perspective - Laurence A. Benner (Washington University Law Quarterly, 1989)
This Article retraces the path of history back to the origins of the privilege against self-incrimination and rediscovers a cluster of rights, embraced by the historical "privilege," which are today no longer associated with the fifth amendment. The central thesis of this Article is that, because of our ignorance of history, we have failed to distinguish analytically between the historical "privilege" against self-incrimination and the relatively more recent right against compulsory self-incrimination. This failure has led to a one-dimensional analysis of self-incrimination issues (focusing solely upon compulsion) which has obfuscated fundamental values underlying once protected by the "privilege," engendered muddled thinking, and given rise to a confused doctrine riddled with anomalies.
Keywords: Self-incrimination; Miranda v. Arizona; 86 S. Ct. 1602